2019
DOI: 10.4236/ojapps.2019.96040
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in <i>Bifidobacterium animalis subsp.lactis BB</i>-12 under Various Atmospheres

Abstract: The influence of relative humidity (RH) on quasistatic current-voltage (I-V) characteristics of Bifidobacterium animalis subsp. lactis BB-12 thin layers was studied for the first time. The value of electrical conductivity in 75% RH was found to be in the order of 10 −7 (ohm•cm) −1 , which was 10 6 orders of magnitude higher than that observed in dry atmosphere. It was concluded that RH played a key role in hysteresis behavior of the measured (I-V) characteristics. FTIR measurements showed that under water mois… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…As we stated in our study [21], this experimental findings showed us that there was no structural transformation under relative humidity. On the other side, increase in the conductivity was interpreted by the increase in the population of charge carries, supplied by the interaction BB-12 with the water moisture, monitored by amine and carboxyl group through FTIR and Zeta potential measurements.…”
Section: Bifidobacterium Bb-12supporting
confidence: 80%
See 1 more Smart Citation
“…As we stated in our study [21], this experimental findings showed us that there was no structural transformation under relative humidity. On the other side, increase in the conductivity was interpreted by the increase in the population of charge carries, supplied by the interaction BB-12 with the water moisture, monitored by amine and carboxyl group through FTIR and Zeta potential measurements.…”
Section: Bifidobacterium Bb-12supporting
confidence: 80%
“…In some experiments, EPS-protein conjugate vaccines could enhance immunogenity [20]. Our studies revealed that the maintenance of the unique electrophysiological properties of BB-12,Infantis in an aerobic environment for up to 6 months could be attributed to the integrity of their unique EPS structure [21]. Hence, the single strain probiotic bifidbacterial polysaccharide cell structure can be considered as a lipopeptide based vaccines.…”
Section: Single Strain Probiotic Bifidobacteria In Vaccine Developmentmentioning
confidence: 83%
“…There are some mechanisms explaining the antiviral impacts of probiotics. A brief report 39 claimed that high-single dose endoscopic administration of appropriate and reliableBifidobacterium Infantis (BB-12 ), as potential probiotic, or use of these strains' lipopolysaccharide membranes in vaccine development especially in patients with gastrointestinal symptoms (diarrhea, abdomen pain, vomiting) can result in more therapeutic and preventive effects in Coronavirus-infected patients 40,41 . Consequently, Bifidobacterium animalistheoretically can inhibit the replication of coronaviruses by reducing ER stress-related autophagy, especially the inositol-requiring enzyme 1 (IRE1) pathway, over its anti interleukin-17 effect 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Our studies indicated that the maintenance of the unique electrophysiological properties of BB-12 in an aerobic environment for up to 6 months could be attributed to the integrity of its EPS. 31 Also, Salazar et al 32 reported that EPS derived from Bifidobacterium animalis sp.lactis exhibited metabolic activity in in vitro conditions. There are two basic types of vaccines; peptide -based vaccines and lipopeptides derived from microbes.…”
Section: Bifidobacteria In the Management Of Covid-19mentioning
confidence: 99%